Analisis Bibliometrik: Tren Penelitian Pendekatan Culturally Responsive Teaching (CRT) Pada Pembelajaran Matematika di Indonesia - Sudrajat (Jurnal Inovasi Pendidikan Matematika (JIPM), 2025)
The increasing research on the culturally responsive teaching (CRT) approach shows that this approach can improve students' abilities and student participation in learning, so that a more in-depth analysis of the results of these studies is needed. Therefore, the purpose of this study is to review the trend of research results on the culturally responsive teaching (CRT) approach to mathematics learning in Indonesia and visualize them. This research method uses eval__uative and descriptive bibliometric analysis. The sample used in this study came from a database of dimensions of 84 published articles that had gone through several stages of data collection. The results showed that the highest number of publications in 2024 was 54 published articles. The top-ranked bibliographic pair of institutions or universities was Padang State University, with a total link strength of 10. The journal bibliographic pair with the largest number of documents was the SHES journal, which had nine published articles. The document bibliographic pair with the most citations was Taher in 2023, with 80 times. The influential bibliographic author in this study was Atmojo, Idam Ragil Widianto. The focus of the research is divided into three, namely the CRT approach, mathematics learning, and students. New themes in this study, namely elementary schools, mathematics learning, learning, teachers, implementation, private and public secondary schools, the DAP approach, Gen Z, STEAM learning, and students' mathematical abilities. These themes can be used for further research because they are still rare in this research topic.